ANALYSIS OF EMPLOYEE MUTATION AND JOB PROMOTION ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION AT THE REGIONAL REVENUE AGENCY NORTH SUMATRA PROVINCE - Merlinda; Mesra B; Elfitra Desy Surya (RADJA PUBLIKA, 2024)
This study aims to analyze the effect of employee transfers and job promotions on employee performance, both directly and through job satisfaction as a mediating variable at the Regional Revenue Agency of North Sumatra Province. Transfers and promotions are part of human resource management that are expected to improve employee motivation and performance. This study uses a quantitative approach with a survey method. Data were collected through questionnaires distributed to 90 respondents who were employees at the agency. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results of the study indicate that employee transfers directly have a positive but insignificant effect on employee performance, but their indirect effect through job satisfaction has a positive and significant effect. Employee transfers also have a positive and significant effect on job satisfaction. Job promotions, both directly and through job satisfaction, have a positive and significant effect on employee performance. Job promotions have a positive and significant effect on job satisfaction, as well as job satisfaction on employee performance also has a positive and significant effect.